2016
DOI: 10.1039/c6ra01311b
|View full text |Cite
|
Sign up to set email alerts
|

Influence of the electrodeposition potential on the crystallographic structure and effective magnetic easy axis of cobalt nanowires

Abstract: Cobalt nanowires (NWs) have been synthesized by electrodeposition inside the pores of anodized aluminium oxide templates, at different values of applied deposition potential.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 35 publications
0
4
0
Order By: Relevance
“…The reason for this is because the sites for dehydration on atomically rough planes are larger in number than smooth planes [119]. The change in phase transformation of Co NWs was seen (i.e., from hcp to fcc) by changing the deposition parameters [120,121,122], and a group of studies by Mukhtar et al [123,124,125,126,127] showed that the smaller grain size of Co favors the formation of fcc Co NWs, and larger grain size favors the formation of hcp Co NWs. Similarly, the mixture of hcp and fcc phases was observed in Co NWs, which seems to crystallize in early stage of deposition, and later with the increase in deposition time as the length of Co NWs increases, they crystallize into the hcp phase [128].…”
Section: Electrodeposition and Structure Of Multi-segmented Nws Inmentioning
confidence: 99%
“…The reason for this is because the sites for dehydration on atomically rough planes are larger in number than smooth planes [119]. The change in phase transformation of Co NWs was seen (i.e., from hcp to fcc) by changing the deposition parameters [120,121,122], and a group of studies by Mukhtar et al [123,124,125,126,127] showed that the smaller grain size of Co favors the formation of fcc Co NWs, and larger grain size favors the formation of hcp Co NWs. Similarly, the mixture of hcp and fcc phases was observed in Co NWs, which seems to crystallize in early stage of deposition, and later with the increase in deposition time as the length of Co NWs increases, they crystallize into the hcp phase [128].…”
Section: Electrodeposition and Structure Of Multi-segmented Nws Inmentioning
confidence: 99%
“…Eventually, polymeric porous templates (e.g., nanoporous polycarbonate membranes) have been utilized, in cases where the use of oxide membranes was found to be not compatible with the electrolytic bath and deposition conditions [139,140]. The investigated magnetic materials comprise single metals (like Fe, Co or Ni) [11,48,51,[141][142][143][144], binary (Co-W, Co-Pt, CoNi, FeNi, etc.) [51,89,106,[144][145][146][147][148][149][150][151][152][153][154] and ternary alloys (e.g., CoNiP) [155].…”
Section: Magnetic Properties Of Nanowiresmentioning
confidence: 99%
“…In any case, the high-aspect ratio of magnetic nanowires usually causes the occurrence of shape anisotropy, making them promising candidates for recording media with perpendicular-to-plane magnetic anisotropy [48,137]. In some cases, particularly for single crystalline nanowires (e.g., Co nanowires), the magnetocrystalline axis of easy magnetization is not oriented along the nanowire axis but perpendicular to it [51,143,163,164]. The competition between shape anisotropy and magnetocrystalline anisotropy causes peculiar angular dependence of the magnetic response in this case.…”
Section: Magnetic Properties Of Nanowiresmentioning
confidence: 99%
“…Magnetic properties of nanostructured materials like Co, Ni, Fe have been widely investigated [1][2][3][4][5][6][7][8][9][10][11][12][13][14]. These studies have usually indicated emergence of novel magnetic and transport properties as the dimension approaches the length scale of a few to tens of nm.…”
Section: Introductionmentioning
confidence: 99%